1967
DOI: 10.1042/bj1050079
|View full text |Cite
|
Sign up to set email alerts
|

The immunochemistry of Shigella flexneri O-antigens. The biochemical basis of smooth to rough mutation

Abstract: 1. Smooth to rough mutation has the same biochemical basis in Shigella as in Salmonella. It is the result of enzyme defects blocking the incorporation of the O-specific side chains that characterize the smooth lipopolysaccharide with the consequent exposure of the underlying basal structures that determine ;rough'-specificity. 2. The Shigella flexneri basal structure resembles its Salmonella analogue in that it has the same qualitative sugar composition, and enzyme defects in its biosynthetic pathway give rise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
3

Year Published

1968
1968
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 19 publications
1
24
0
3
Order By: Relevance
“…In other groups of bacteria, however, the core structure may be different [18,20,50,50aPc3. It has been shown that occasionally different core structures carry identical 0-specific chains 150bl. Similarly, structural differences exist in the lipid A component of other genera with respect to the glucosamine disaccharide 1581 as well as to the fatty acids [59-621.…”
mentioning
confidence: 99%
“…In other groups of bacteria, however, the core structure may be different [18,20,50,50aPc3. It has been shown that occasionally different core structures carry identical 0-specific chains 150bl. Similarly, structural differences exist in the lipid A component of other genera with respect to the glucosamine disaccharide 1581 as well as to the fatty acids [59-621.…”
mentioning
confidence: 99%
“…Unerwartet ist auflerdem, da13 in allen Fraktionen 6-5013 nach HNO,-Abbau nur noch Glucose in groSeren Mengen nachweisbar war. Hier lie13 die bisher angenommene Struktur (JOHNSTON et al 1967) einen deutlichen Anstieg der Galaktosewerte erwarten.…”
Section: Diskuseionunclassified
“…Jlexneri R-LPS preparations (Johnston et al, 1968), those of rough serotypes la-R, 2a-R, 3a-R, 4a-R,, 4a-R2, 5-R and variant X-R contained free side-chains bound together as in the 0-specific structures, because they precipitated with the homologous smooth S . Jlexneri antiserum.…”
Section: Structure Of the Basal Region Of Sj-lexneri Lipopolysaccharmentioning
confidence: 99%